The Use of Mystery Envelope Game in Learning to Write Simple Mandarin Sentences among Twelfth Grade Students at SMA Insan Cendekia Syech Yusuf Gowa - Nurmiati Nurmiati; Misnah Mannahali; Nur Nasharuddin Noni (Universitas Negeri Surabaya, 2025)
This study investigates the implementation of the Mystery Envelope game as an interactive method to enhance Mandarin sentence-writing skills among twelfth-grade students at Insan Cendekia Syech Yusuf Senior High School, Indonesia. Students commonly face difficulties in constructing grammatically correct and coherent Mandarin sentences, despite strong memorization abilities, especially those from Islamic boarding school backgrounds. This research uses Classroom Action Research (CAR) across two cycles, applying both qualitative and quantitative methods, including observation sheets, field notes, and pre- and post-tests. The Mystery Envelope game involved students forming sentences from randomly selected Mandarin words contained in envelopes, encouraging critical thinking and grammar application in a fun, student-centered environment. Results revealed a significant improvement in writing ability: the average score increased from 86,5 in Cycle I to 87,6 in Cycle II. Students demonstrated better understanding of sentence structure, vocabulary usage, and confidence in writing. The study concludes that the Mystery Envelope game is an effective, engaging instructional strategy for improving Mandarin writing skills, particularly in constructing simple sentences. It also enhances student motivation, participation, and language mastery through active learning techniques.